Lepromatous leprosy in Saudi female from central region - al-Majed, S (Journal of hygiene, epidemiology, microbiology, and immunology, 1991)
Leprosy is an uncommon disease in Saudi population. Lepromatous leprosy is a most contagious form of leprosy. Erythema nodosum leprosum is an unusual complication of leprosy. We report an unusual case of leprosy from the central region of Saudi Arabia presenting as erythema nodosum leprosum.
Keywords: Leprostatic Agents; Saudská Arábie; Saudi Arabia; Female; Aged; Erythema Nodosum; erythema nodosum; ženské pohlaví; lepromatózní lepra; Humans; senioři; lidé; kombinovaná farmakoterapie; leprostatika; Drug Therapy, Combination; Leprosy, Lepromatous